PERANCANGAN AWAL INSTALASI AIR BUANGAN PENDINGIN MENGGUNAKAN MULTISTAGEFLASH RECYLE DISTILLATION (STUDI KASUS PT. INDONESIA POWER PELABUHAN TANJUNG EMAS SEMARANG) - Nurandani Hardyanti; Syafrudin Syafrudin; Inri Natalia Inri Natalia (TEKNIK, 2007)
The port of Tanjung Emas Semarang was located at the coast needed more clean water for shipping,industries and the communities. The production process of PLTU Indonesia Power produced waste wateras cooling water that caused thermal pollution. Considering the quality, quantity, and continuity of thatwaste water used as one of alternative source of clean water. It treated using by multistageflash recycleddistillation method. The purpose of this plant to fulfill clean water for shipping and port of Tanjung Emasarea with production capacity was 50 liters per seconds for duration planning about 15 years. The locationof this plant was next to PT. SRIBOGA with area 8000 m2, wherein the intake on the Canal of PLTUIndonesia Power. In order to fulfill the quality of water, this plant used oil separator and antiscalant aspretreatment. Production cost of distillation plant was Rp 13.647 per m3. This cost was too expensive so itrequired to be done crossed subsidy. The price of clean water was Rp 2000 /m3 for public, Rp 5500 per m3for industries and Rp 3000 per m3 for governmental office.